Pathobiological Determinants of Atherosclerosis in Youth (PDAY) Risk Score in Young Adults Predicts Coronary Artery and Abdominal Aorta Calcium in Middle Age: The CARDIA Study. Issue 2 (12th January 2016) - Gidding, Samuel S.; Rana, Jamal S.; Prendergast, Christopher; McGill, Henry; Carr, J. Jeffery; Liu, Kiang; Colangelo, Laura A.; Loria, Catherine M.; Lima, Joao; Terry, James G.; Reis, Jared P.; McMahan, C. Alex
Abstract : Background—: We explored whether, the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) coronary and abdominal risk scores measured at 18 to 30 years of age and changes in these scores would more strongly predict coronary artery calcium (CAC) and abdominal aortic calcium (AAC) assessed 25 years later, than scores measured 25 years later. Methods and Results—: In the Coronary Artery Risk Development in Young Adults (CARDIA) study, 3008 participants had measurements of risk score components at 5-year intervals beginning at 18 to 30 years of age. CAC and AAC were assessed at 43 to 55 years of age. Odds ratios (ORs) for the presence and extent of CAC/AAC per/point higher score and c-statistics for predicting CAC/AAC were calculated. The prevalence of CAC was 28% and AAC was 53%. For each 1 point higher PDAY score, the odds of CAC were higher using baseline scores than year 25 scores (OR, 1.29; 95% confidence interval [CI], 1.25–1.33 versus OR, 1.12; 95% CI, 1.11–1.14). For AAC, ORs at years 0 and 25 were similar (OR, 1.29; 95% CI, 1.24–1.34 versus OR, 1.22; 95% CI, 1.19–1.26). C-statistic for CAC prediction was higher at year 0 than year 25 (0.731 versus 0.705) but similar at years 0 and 25 for AAC (0.665 versus 0.670). ORs for CAC were highest at baseline, and, for AAC, ORs were highest at year 10. Including change in PDAY scores with baseline scores improved prediction. Conclusions—: Atherosclerosis risk and change in risk assessed in young adulthood years before subclinical atherosclerosis imaging provide strong prediction of future subclinical atherosclerosis. CAC and AAC reflect chronic risk exposure in addition to risk measured at the time of study.